2012
DOI: 10.1002/em.21707
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow genotoxicity of 2,5‐dimethylfuran, a green biofuel candidate

Abstract: 2,5-Dimethylfuran (DMF) is being considered as a potential green transportation biofuel, but there is limited information about its toxicity and safety. We examined DMF toxicity in the bone marrow using a murine in vitro erythropoietic micronucleus assay and found that exposure to DMF (0.1 mM, 1 hr) induced an increase in micronuclei frequency compared with controls. These data suggest that DMF may be genotoxic to hematopoietic cells and that more thorough toxicological studies on DMF should be conducted to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…We found that FA induced MN in mouse PCEs in a dose-dependent manner. MN in mouse PCEs is a widely used biomarker for genotoxicity (Fromowitz et al, 2012; Hayashi et al, 1994) and MN frequency in human peripheral lymphocytes has been associated with cancer risk (Bonassi et al, 2011). Our finding shows that FA is genotoxic to mouse HSC/HPC in vitro , suggesting that chromosomal damage may be one potential mechanism underlying FA induced leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that FA induced MN in mouse PCEs in a dose-dependent manner. MN in mouse PCEs is a widely used biomarker for genotoxicity (Fromowitz et al, 2012; Hayashi et al, 1994) and MN frequency in human peripheral lymphocytes has been associated with cancer risk (Bonassi et al, 2011). Our finding shows that FA is genotoxic to mouse HSC/HPC in vitro , suggesting that chromosomal damage may be one potential mechanism underlying FA induced leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse erythropoietic culture method was detailed previously (Fromowitz et al, 2012; Shuga et al, 2007). In brief, bone marrow (BM) cells were isolated from the hind legs of C57BL/6J mice and were labeled with biotin-conjugated α-Lin Abs, consisting of α-CD3e, α-CD11b, α- CD45R/B220, α-Ly6G/Ly6C, and α-TER-119 Abs (2 µl of each Ab/10 6 cells; BD Pharmingen, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently however, in vitro studies on erythropoietic micronucleus assay exposed to 0.1 mM DF for an hour, showed an increase in micronuclei, suggesting a genotoxic effect on the bone marrow (Fromowitz et al 2012). Not much is known yet of the toxicity of DMF to human health because of scanty environmental testing.…”
Section: Unregulated Emissionsmentioning
confidence: 99%
“…In vitro exposure to DMF led to the induction of micronuclei in murine bone marrow cells (8). DMF tested negative in the Ames tests (9,10), but tested positive in the rec-assay using Bacillus subtilis bacteria (11).…”
Section: Introductionmentioning
confidence: 99%